First there was forever : a novel - Romano, Juliana (2015)
Los Angeles, California, tenth-graders Lima and Hailey have always been best friends, but now Hailey is chasing after a more popular crowd, and Lima connects not only with a different popular group, she also begins getting close to Hailey's long-term crush, Nate.
Keywords: Best friends -- Fiction; Friendship -- Fiction; Conduct of life -- Fiction; Popularity -- Fiction; High schools -- Fiction; Schools -- Fiction; Families -- California -- Fiction; Malibu (Calif.) -- Fiction; Electronic books; Fiction